2008
DOI: 10.1124/jpet.108.147884
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral and Neurochemical Effects of a Novel d-Amino Acid Oxidase Inhibitor Compound 8 [4H-Thieno [3,2-b]pyrrole-5-carboxylic Acid] and d-Serine

Abstract: Multiple studies indicate that N-methyl-D-aspartate (NMDA) receptor hypofunction underlies some of the deficits associated with schizophrenia. One approach for improving NMDA receptor function is to enhance occupancy of the glycine modulatory site on the NMDA receptor by increasing the availability of the endogenous coagonists D-serine. Here, we characterized a novel D-amino acid oxidase (DAAO) inhibitor, compound 8 [4H-thieno [3,2-b]pyrrole-5-carboxylic acid] and compared it with D-serine. Compound 8 is a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 38 publications
5
70
0
Order By: Relevance
“…Adage's group reported a slight increase in D-serine levels in rat brain following intravenous administration of a pyrazole-3-carboxylate based DAAO inhibitor (AS057278) alone [39], indicating that this effect may be due to its ability to penetrate the blood-brain barrier. Furthermore, Smith et al [40] have developed the novel DAAO inhibitor 4H-thieno[3,2-b]pyrrole-5-carboxylic acid (IC 50 =145 nM for human, IC 50 =114 nM for rat). This compound failed to significantly influence amphetamine-induced psychomotor activity, nucleus accumbens dopamine release, or (+)-MK-801 (dizocilpine)-induced deficit in novel object recognition in rats, suggesting that acute inhibition of DAAO by this compound appears not to be sufficient to increase D-serine to concentrations required to produce antipsychotic and cognitive enhancing effects similar to those observed after administration of high doses of D-serine [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adage's group reported a slight increase in D-serine levels in rat brain following intravenous administration of a pyrazole-3-carboxylate based DAAO inhibitor (AS057278) alone [39], indicating that this effect may be due to its ability to penetrate the blood-brain barrier. Furthermore, Smith et al [40] have developed the novel DAAO inhibitor 4H-thieno[3,2-b]pyrrole-5-carboxylic acid (IC 50 =145 nM for human, IC 50 =114 nM for rat). This compound failed to significantly influence amphetamine-induced psychomotor activity, nucleus accumbens dopamine release, or (+)-MK-801 (dizocilpine)-induced deficit in novel object recognition in rats, suggesting that acute inhibition of DAAO by this compound appears not to be sufficient to increase D-serine to concentrations required to produce antipsychotic and cognitive enhancing effects similar to those observed after administration of high doses of D-serine [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Smith et al [40] have developed the novel DAAO inhibitor 4H-thieno[3,2-b]pyrrole-5-carboxylic acid (IC 50 =145 nM for human, IC 50 =114 nM for rat). This compound failed to significantly influence amphetamine-induced psychomotor activity, nucleus accumbens dopamine release, or (+)-MK-801 (dizocilpine)-induced deficit in novel object recognition in rats, suggesting that acute inhibition of DAAO by this compound appears not to be sufficient to increase D-serine to concentrations required to produce antipsychotic and cognitive enhancing effects similar to those observed after administration of high doses of D-serine [40]. In contrast, there is no correlation between the distribution of DAAO and NMDA receptors in the brain [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Both MPC and Compound 8 (each 100 μM) could completely attenuate the DAAO activity ( Figure 6). It has been reported that the IC 50 value of Compound 8 is 114 nM (17), while that of MPC is 0.91 μM (12), indicating that Compound 8 is a more potent inhibitor of DAAO activity. However, the results from this study ( Figure 6) indicated that both specific inhibitors (100 μM) appropriately inhibited the DAAO activity.…”
Section: Inhibition Of Brain Daao Activity By Specific Inhibitorsmentioning
confidence: 99%
“…To assess DAAO activity in rat brain tissues, the brain tissue homogenates were centrifuged as previously described (15,17), and the pellet fraction was then used as an enzyme source for the proposed assay. Increasing concentrations of D-KYN were added to the reactions to determine its optimum concentration as a substrate, which was set at the plateau level of 7.0 mM (Figure 2).…”
Section: Daao Activitymentioning
confidence: 99%
See 1 more Smart Citation